ELATIHAN MENULIS ARTIKEL BERTEMA PENDIDIKAN KARAKTER BAGI GURU SMP NEGERI 4 SINGOROJO KABUPATEN KENDAL JAWA TENGAH - Sunahrowi, Sunahrowi; B.P, Alfariz Firdausya (Badan Pengembang Konservasi UNNES, 2017)
The National Goal set forth in the Preamble of the 1945 Constitution of the State of the Republic of Indonesia is to promote the common welfare, to educate the life of the nation, and to participate in the implementation of world order based on eternal peace and social justice. To realize these national goals, education is a crucial factor. The world of education consists of (maha) students, facilities and infrastructure, and of course educators (teachers). With regard to several main points about national education, one of the important competencies possessed by teachers is the ability to write scientific articles. The ability to write scientific articles for teachers has at least two practical benefits; first, the ability to write scientific articles can support the professionalism of teachers as individuals and also as well as educators. Second, the ability to write scientific articles also provide benefits for learners because a teacher who is skilled in scientific writing indicates that the teacher has a high degree of innovation and creativity and can support the success of teaching and learning activities. Some of the above demands leave many contradictions in practice in the school environment, especially junior high school teachers in Singorojo District of Kendal. Many educators have not been able to write scientific (scientific articles) even though they often encounter problems in everyday teaching. Thus, the low ability to write scientific articles for teachers is not based on the absence of material (problems) but caused by lack of training for them. Based on the problem, it is a necessity to conduct training of scientific article writing for teachers and integrate it with some advanced techniques, in this training choose Focus Group Discussion (FGD) technique. Focus Group Discussion (FGD) is a systematic effort in collecting data and information.